2016
DOI: 10.1002/jat.3337
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the affinity constant for perchlorate binding to the sodium‐iodide symporter based on in vitro and human in vivo data

Abstract: A series of previously published physiologically based pharmacokinetic (PBPK) models describe the effect of perchlorate on iodide uptake by the thyroid, with the mechanism being competitive inhibition of iodide transport by the sodium-iodide symporter (NIS). Hence a key parameter of these models is the affinity of perchlorate for the NIS, characterized as the Michaelis-Menten kinetic constant, K . However, when model predictions were compared to published results of a human study measuring radio-iodide uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Recent revision of the affinity constant for perchlorate binding to the NIS symporter based on in vitro and human in vivo data, performed by refitting published in vitro data, in which perchlorate-induced inhibition of iodide uptake via the NIS was measured, yielding a Michaelis-Menten kinetic constant (Km) of 1.5 μm, showed that a 60% lower value for the Km, equal to 0.59 μm. Substituting this value into the PBPK model for an average adult human significantly improved model agreement with the human RAIU data for exposures <100 μg kg-1 day-1 (Schlosser PM, 2016).…”
Section: Evidence Supporting This Ker Biological Plausibilitymentioning
confidence: 90%
“…Recent revision of the affinity constant for perchlorate binding to the NIS symporter based on in vitro and human in vivo data, performed by refitting published in vitro data, in which perchlorate-induced inhibition of iodide uptake via the NIS was measured, yielding a Michaelis-Menten kinetic constant (Km) of 1.5 μm, showed that a 60% lower value for the Km, equal to 0.59 μm. Substituting this value into the PBPK model for an average adult human significantly improved model agreement with the human RAIU data for exposures <100 μg kg-1 day-1 (Schlosser PM, 2016).…”
Section: Evidence Supporting This Ker Biological Plausibilitymentioning
confidence: 90%
“…In the case of iodine blockade, the two competing entities are chemically identical (radioiodine and stable iodine) and share the same Michaelis–Menten constant ( K m = 9 µmol l −1 ). For perchlorate, the Michaelis–Menten constant has been given with 1.5 µmol l −1 (Kosugi et al 1996 ), but a revised lower value of 0.59 µmol l −1 was reported recently with the indication that the latter was better suited to describe the kinetics of lower dose levels below 100 µg kg −1 day −1 (Schlosser 2016 ). When validating our model using empirical data, we used both constants to identify the value actually better suited to study protective effects against radioiodine exposure.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we used the complete combined perchlorate-radioiodine model with competition at the carrier site to compute the protective efficacy after the experimental administration of radioiodine (iodine-123) to volunteers as described in several studies (Lawrence et al 2000 ; Greer et al 2002 ; Bravermann et al 2005 ; Hänscheid et al 2011 ) and compared our results with the measured values reported. Computations were performed for Michaelis–Menten constants for perchlorate described in the literature: 1.5 µmol l −1 (Kosugi et al 1996 ) or 0.59 µmol l −1 , as recently reported for lower dosages up to 100 µg kg −1 day −1 (Schlosser 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…NIS exclusively transports monovalent anions, encompassing a wide range of substrates including BF 4 -, TcO 4 -, and SCN - (Table 1. References reporting uptake, inhibition, stoichiometry and K m : [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. References reporting fresh and seawater anion concentrations: .)…”
Section: Introductionmentioning
confidence: 99%
“…In rat NIS, iodide is transported with a K m value of 9.7-33 μM [13,16,17]. [13,16,18]. No mechanism has been identified to explain the different affinities for these chemically similar anions.…”
Section: Introductionmentioning
confidence: 99%